1969
DOI: 10.1530/acta.0.0610255
|View full text |Cite
|
Sign up to set email alerts
|

Studies With 4-14c-Lynestrenol in Normal and Lactating Women

Abstract: 4-14C-Lynestrenol** was administered either orally or by intravenous injection to women using Lyndiol®*** (5 mg lynestrenol + 150 μg mestranol). In order to study the effect of the pharmaceutical form in oral administration, the radioactive progestagen was given either as the pure compound in the form of a gelatin capsule or as a tablet containing all the ingredients usually present in Lyndiol®-tablets. The concentration of radioactivity in the blood and the excretion of radioactivity in the urine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1971
1971
1983
1983

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The figures for the urinary and faecal excretion of radioactivity after an oral Org 2969 dose are in the same range as reported for the other orally active progestagens (Layne et al 1963;Cooper & Kellie 1968;van der Molen et al 1969;Dorfman 1971;Gerhards et al 1971;Kishimoto et al 1972a,b).…”
Section: Discussionsupporting
confidence: 77%
“…The figures for the urinary and faecal excretion of radioactivity after an oral Org 2969 dose are in the same range as reported for the other orally active progestagens (Layne et al 1963;Cooper & Kellie 1968;van der Molen et al 1969;Dorfman 1971;Gerhards et al 1971;Kishimoto et al 1972a,b).…”
Section: Discussionsupporting
confidence: 77%
“…Odlind et al (1979a) reported peak plasma norethisterone concentrations at 2 hours after oral doses of 0.5mg and 5mg oflynoestrenol, and Siekmann et al (1980) found peak plasma concentrations of norethisterone of 15 ng/ml after an oral dose of 2.Smg lynoestrenol. Van der Molen et al (1969) also examined the passage of radioactivity into the breast milk of women receiving a dose of 14C-Iynoestrenol. During long term therapy with lynoestrenol, plasma concentrations of norethisterone rise to greater levels than expected due to an effect on the SHBG capacity, but this was only seen if the dose was greater than 600#g daily (Odlind et aI., 1980).…”
Section: Lynoestrenolmentioning
confidence: 99%
“…With respect to the transfer studies using radioactive isotopes, these appear to have been done in the immediate post-partum week before lactation could be fully established, and since suckling had to be avoided, milk volumes where quoted tended to be low. Although the Laumas et al (1967) study, in which milk volumes obtained were not mentioned, indicated that up to 1-5% of the administered radioactive dose may be secreted in the milk, other studies by Van der Molen et al (1969) and Wijmenga et al (1969) in which milk volumes obtained were quoted have reported lower percentage recovery rates. It would be perhaps more important to undertake such studies after lactation has been fully established in mothers about to wean their infants, say around two months post-partum.…”
Section: Discussionmentioning
confidence: 93%